Los psicólogos hispanohablantes y la teoría de Alfred Adler en la revista Internationale Zeitschrift fuer Individualpsychologie (1914-1937) - León Donayre, Ramón (2000)
This paper deals with the reception of and information about the publication of Latin American and Spanish authors(between 1914 and 1937) in the pages of the Iruernationale Zeitschrift fuer Individualpsychologie, the official journal of the Adlerian movement. Lydia Sicher was the mosractive reviewer of Spanish literature. Oliver Brachfeld, later ah émigré.toLatin America, was an prolific contributor, also. The forms and ways for the diffusion of the Latin American authors in Europe and the fate of Adlerian ideas in Latin America are briefly cornmented.